2020
DOI: 10.21203/rs.3.rs-34570/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is the effect of stimulus complexity on attention to repeating and changing information in Autism?

Abstract: Background Previous research has suggested that atypical attention in autism might be driven by a preference for sameness over novelty. There is also evidence of slower habituation to a repeating stimulus in autism. It is not known whether slower habituation is driven by atypically slower processing of repeating information or whether it is a manifestation of an attentional bias away from novelty towards sameness. Methods We adapted an existing eye-tracking task and measured eye movements to two streams of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Novelty does not appear to stimulate the same degree of curiosity and exploration in autism that it does in typical development (Anckarsäter et al, 2006;Arora et al, 2021;Vivanti et al, 2018).…”
Section: Early Learning In Autismmentioning
confidence: 86%
See 3 more Smart Citations
“…Novelty does not appear to stimulate the same degree of curiosity and exploration in autism that it does in typical development (Anckarsäter et al, 2006;Arora et al, 2021;Vivanti et al, 2018).…”
Section: Early Learning In Autismmentioning
confidence: 86%
“…Autistic children often show increased attentional engagement with specific objects or parts of objects, and increased amount of time spent in repetitive objectoriented routines compared to their non-autistic peers (Fanning et al, 2021;McKinnon et al, 2019;Ozonoff et al, 2008). Additionally, experimental studies have documented that autistic preschoolers, unlike their peers with typical development or other neurodevelopmental conditions, do not show a preferential attention towards novel versus repeated stimuli (Arora et al, 2021;Vivanti et al, 2018).…”
Section: Contributing To An Atypical Balance Of Assimilation/accommod...mentioning
confidence: 99%
See 2 more Smart Citations
“…A large proportion of the children recruited to the SAAND study also took part in this eye tracking study. Detailed methods and results from the SAAND study are reported elsewhere ( 24 , 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%